PENDIDIKAN KESEHATAN BERPENGARUH TERHADAP TINGKAT PENGETAHUAN SISWA TENTANG RESUSITASI JANTUNG PARU - Yuliana; Citra Sepriana; Antoni Eka Fajar Maulana; Nia Firdianty Dwiatmojo; Ni Nyoman Santi Tri Ulandari (LPPM STIKES Mataram, 2024)
Introduction: Cardiac arrest has become a major problem that continues to grow globally, including in Indonesia. When there is a victim of cardiac arrest, people who are near the victim have a very big role to perform CPR (Cardiopulmonary Resuscitation) quickly. Knowledge of CPR skills is very important to be known and carried out by the general public. So one effort to increase and improve this knowledge is through health education. Objective: To determine the effect of health education on the level of student knowledge about cardiopulmonary resuscitation at SMAN 9 Mataram. Method: The research design used in this study was Pre-experiment through one group pre- test-post-test design approach. The population in this study were all students of class X SMAN 9 Mataram totaling 374. The sample in this study amounted to 193 respondents. The instrument used was a questionnaire. Data analysis used Paired Simple T-test. Results: The level of student knowledge before and after being given health education about Hands Only CPR (Cardiopulmonary Resuscitation) increased, from the number of good categories 17% to 85%. The Paired Simple T-test obtained a significant value of P valued = 0.000. Conclusion: There is an influence of health education on the level of students' knowledge about CPR at SMAN 9 Mataram.